PERANCANGAN DAN PEMBUATAN PROTOTYPE SHANK PROSTHESES KAKI BAGIAN BAWAH LUTUT - Prakoso, Agung (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2016)
The existence o f fe e t as the part of the human body is very important to support the daily activities which is to support the body and to walk. The lost of the under knee part (amputation) is the dominant case of the total cases of amputation in Indonesia. So that we need a tool to restore the balance of the human body to be able to do our daily activity. The tool is called prostheses. The design and manufacture of prototypeshank prostheses under knee is intended for persons who have 162 cm height and 57 Kg of average weight. Prostheses are aimed to the persons who only lost one limb below the knee. In this design, the length of the shank can be set according to the length of leg amputated and is intended to persons who are still experiencing high growth (teenager). The material is stainless steel 316L. The shank has a length 200-300 mm, width 67 mm and 2 mm thick.